2022
DOI: 10.3390/ijms23042219
|View full text |Cite
|
Sign up to set email alerts
|

Novel Role of Ghrelin Receptor in Gut Dysbiosis and Experimental Colitis in Aging

Abstract: Chronic low-grade inflammation is a hallmark of aging, which is now coined as inflamm-aging. Inflamm-aging contributes to many age-associated diseases such as obesity, type 2 diabetes, cardiovascular disease, and inflammatory bowel disease (IBD). We have shown that gut hormone ghrelin, via its receptor growth hormone secretagogue receptor (GHS-R), regulates energy metabolism and inflammation in aging. Emerging evidence suggests that gut microbiome has a critical role in intestinal immunity of the host. To dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 76 publications
3
12
0
Order By: Relevance
“…Consistent with a role for endogenous ghrelin in intestinal homeostasis, we recently showed that deletion of its receptor growth hormone secretagogue receptor (GHS-R) led to gut dysbiosis in an age-dependent manner, and also showed increased susceptibility to DSS-induced colitis. 62 At the phylum level, the ratio of Firmicutes and Bacteroidetes (F/B ratio) was similar in young but increased in older GHS-R KO mice. At the family level, young GHS-R KO mice showed lower Lachnospiraceae and Prevotellaceae , but higher Erysipelotrichaceae .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Consistent with a role for endogenous ghrelin in intestinal homeostasis, we recently showed that deletion of its receptor growth hormone secretagogue receptor (GHS-R) led to gut dysbiosis in an age-dependent manner, and also showed increased susceptibility to DSS-induced colitis. 62 At the phylum level, the ratio of Firmicutes and Bacteroidetes (F/B ratio) was similar in young but increased in older GHS-R KO mice. At the family level, young GHS-R KO mice showed lower Lachnospiraceae and Prevotellaceae , but higher Erysipelotrichaceae .…”
Section: Discussionmentioning
confidence: 92%
“…63 In addition, DSS-induced colitis was exacerbated in both young and older GHS-R KO mice, with older GHS-R KO showing more severe disease activity than young GHS-R KO mice. 62 Collectively, these data suggested that endogenous ghrelin signaling has an important role in maintaining intestinal homeostasis.…”
Section: Discussionmentioning
confidence: 96%
“…For instance, with the highest relative abundance of microbiota, Bacteroidetes was increased and Firmicutes was decreased by DSS. The increase of Bacteroidetes and the ratio of Bacteroidetes / Firmicutes are the indicators of IBD ( 17 , 46 , 47 ). Our results showed that BBR can decrease Bacteroidetes and increase Firmicutes in DSS-induced cats.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, an in vitro study expounded that exogenous ghrelin prevents gastric mucosal inflammatory responses to Helicobacter pylori by controlling p38 phosphorylation and Src/Akt‐dependent up‐regulation of constitutive nitric oxide synthase 98 . Additionally, the lack of GHSR exacerbates dextran sulfate sodium (DSS)‐induced acute colitis in GHSR knockout mice by increasing the levels of inflammatory cytokines and reducing gap junction proteins, consistent with colonic inflammation and intestinal permeability 81 . Moreover, other previous studies have shown that the administration of ghrelin decreases inflammation‐induced colorectal carcinogenesis in mice 99 …”
Section: Ghrelin Regulates Inflammation In Gastrointestinal Diseasesmentioning
confidence: 99%